Prognostic Factors for Conversion to Arthroplasty after Hip Arthroscopy. Review of the Literature - Seijas, Roberto; Barastegui, David; Montaña, Ferran; Rius, Marta; Cuscó, Xavier; Cugat, Ramón (The Surgery Journal, 2021)
Arthroscopic techniques in the treatment of femoroacetabular impingement have experienced an exponential increase over recent years for both diagnosis and treatment. The main risks with treatment are poor clinical outcomes and the conversion to prosthesis. Better knowledge and understanding of the various risk factors leading to prosthesis will improve patient selection for arthroscopic treatments rendering better results. The published papers that have been selected are related to series of hip arthroscopies with risk factors that lead to total hip arthroplasty (THA), in the PubMed database, without a time limit, number of patients, or follow-up time. We selected over 302 papers, 19 papers that show risk factors for conversion to THA. The main risk factors found were femoral chondropathy grade III/IV (relative risk 58.1–12 times increased), acetabular (20–2.96 times), an articular space <2 mm (39–4.26 times), age (14.6–1.06 times), Tönnis 2 in radiographic studies (7.73–3.1 times), obesity (5.6–2.3 times), and osteoarthritis (4.6–2.4 times). There are several risk factors which in an isolated way, highly increase the risk of THA. Some of them have a clear relationship (chondropathy, reduced joint space, Tönnis 2, and osteoarthritis). Based on the review we observed that the elements that are most associated with a conversion to THA after a hip arthroscopy are a high degree of femoral and acetabular chondropathy, a reduced joint space below 2 mm, older age, Tönnis 2, obesity, and hip osteoarthritis.
Keywords: hip arthroscopy; prognostic; prognostic factor; total hip replacement; conversion; arthroplasty